Relationship between speech intelligibility and listener effort in Malayalam-speaking individuals with hypokinetic dysarthria - Santosh Maruthy, Nimisha Raj (Speech, Language and Hearing, 2014)
Several attempts have been made to describe the perceptual characteristics of dysarthria. However, a large majority of these studies are in English, and hence there is a need to investigate dysarthric characteristics in other languages which have a rhythmic structure different than English. The objectives of this study were multifold. First, to describe the perceptual characteristics of hypokinetic dysarthria (HD) in Malayalam- (mora-timed language) speaking individuals. Second, to examine the effect of HD on the listeners’ ratings of speech intelligibility and listener effort. Third, to investigate the relationship between speech intelligibility and listener effort, and fourth to study the effect of listeners’ experience on the ratings of speech intelligibility and listener effort. Five sentences were recorded from eight Malayalam speakers with HD, and eight control speakers. These sentences were played to 10 naïve and 10 expert listeners. Listeners performed the following tasks: describing perceptual characteristics of HD, rating sentence intelligibility, and listener effort. Results showed that the most deviant perceptual characteristics were those related to articulation and rhythm. Lower speech intelligibility and increased listener effort were observed for individuals with HD than control speakers. Speech intelligibility proved to be a strong predictor of listener effort. Experience of the listener had no effect on speech intelligibility ratings, but showed a significant effect for listener effort ratings.